1016 Multiple Sleep Disturbances and Hypertension Risk Among White, Black, and Hispanic/Latina Women. (27th May 2020) - Lunyera, J; Park, Y M; Ward, J B; Gaston, S A; Bhavsar, N A; Muntner, P; Sandler, D P; Jackson, C L
Abstract: Introduction: Poor sleep has been associated with a higher risk of hypertension, but few prospective studies have included multiple sleep dimensions and few have investigated age differences or racial/ethnic disparities in this relationship among pre- and post-menopausal women. Methods: To investigate the association between sleep disturbances and hypertension risk, we used data from women in the United States enrolled in the Sister Study who were aged 35 to 74 years at baseline (2003 to 2009) and did not have hypertension at enrollment. Participants were followed through September 2017. Sleep duration, inconsistent weekly sleep patterns, sleep debt, frequent napping, and insomnia symptoms were reported at baseline. During follow-up, participants reported whether they were diagnosed by a healthcare provider with hypertension. Adjusting for sociodemographic characteristics, health behaviors, and health conditions including diabetes and depression, we used Cox Proportional Hazards regression to estimate hypertension risk among women with vs. without unfavorable sleep characteristics. We also investigated potential modification by race/ethnicity, age, and menopausal status. Results: Of 33, 175 women without hypertension at baseline (mean age ± standard deviation: 53.9 ±8.8 years; 88.8% White, 6.4% Black, and 4.9% Hispanic/Latina), 19.9% developed hypertension over a median follow-up of 9.2 years (interquartile range: 7.6 to 10.9). After adjustment, insomnia symptoms (hazard ratio[HR]=1.08 (95% Confidence Interval [CI]: 1.03-1.15)) and insomnia symptoms combined with short sleep (HR=1.14 (95% CI: 1.06-1.23)) were associated with incident hypertension. While similar across race/ethnicity, these associations were stronger in younger (age <54 vs. ≥54 years) and premenopausal vs. postmenopausal women (p-values for interaction <0.05). Conclusion: Sleep disturbances related to insomnia were associated with an increased risk of hypertension, especially among younger and premenopausal women. Support: This work was funded by the Intramural Program at the National Institutes of Health (NIH), National Institute of Environmental Health Sciences (NIEHS, Z1AES103325-01 [CLJ] and Z01 ES044005 [DPS]).